The Palestinian health research system: who orchestrates the system, how and based on what? A qualitative assessment - Mohammed AlKhaldi; Abdulsalam Alkaiyat; Yehia Abed; Constanze Pfeiffer; Rana Halaseh; Ruba Salah; Manar Idries; Said Abueida; Ibrahim Idries; Ibrahim Jeries; Hamza Meghari; Ali Shaar; et al. (BMC, 2018)
Abstract Background In 2011, the WHO Eastern Mediterranean Region committee launched a strategy for scaling up research in the region to address the countries' health needs through formulating and analysing the National Health Research System (HRS). Stewardship comprises three functions, namely governance, policy and priorities, and is a central pillar of this system to ensure a well-organised and functioning HRS. This study aims to examine the perceptions of the HRS performers to understand these functions and to generate insights for system strengthening. Methods The study was carried out in Palestine, targetting three sectors in the health field, including relevant governmental health institutions, schools of public health, and major local and international health agencies. The data were collected through 52 in-depth interviews (IDIs) and 6 focus group discussions (FGDs) with policy-makers, academics, directors, and experts. Participants and institutions were selected purposively based on a set of criteria and peer review. Results A total of 104 experts participated in the IDIs (52 participants) and FGDs (52 participants in 6 FGDs), highlighting that stewardship functions remain problematic and insufficiently performed, mainly due to a missing health research structural and regulatory framework and dispersed health research work. Despite the limited good practices, the majority of the participants described the Ethical Review and Clearance as weak due to the lack of an agreed-upon national committee and procedural quality and ethics guidelines for non-compliance. A policy or strategy dedicated to health research is lacking. The exercises of research priority-setting appear to be evolving despite the lack of consensus and the low levels of knowledge and experience in research prioritisation. Common gaps, such as weak political will and capacity support, the absence of a national unified regulating body, and the indirect effects of political conditions on strengthening the HRS as well as other sectors, also emerged. Conclusions The stewardship functions of the Palestinian HRS remain weak along with substantial political, structural, and resources and capacity gaps. The study emphasises the imperative need to initiate strategic efforts led by the MOH and the Palestinian National Institute of Public Health alongside with other players to strengthen a national HRS through improving the stewardship functions. To achieve this, attention and support of decision-makers, involvement, mobilisation and strategic dialogue are indispensable, in order to embark on building a well-regulated and coordinated structure, operational research policy, and prioritisation of essential research.